Building muscle and performance a program for size, strength & speed - Tumminello, Nick (Human Kinetics, 2016)
Muscle & Performance offers a unique approach to specialized training that results in improved sport performance through increased strength, power, speed, agility, and endurance, while sculpting a lean and muscular physique. Readers will learn how to get a body that looks and works great.